2001
DOI: 10.1053/jhep.2001.26633
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinomas in native livers from patients treated with orthotopic liver transplantation: Biologic and therapeutic implications

Abstract: The gross and histopathologic characteristics of 212 nonfibrolamellar hepatocellular carcinomas (HCCs) discovered in native livers removed at the time of liver transplantation were correlated with features of invasive growth and tumorfree survival. The results show that most HCCs begin as small well-differentiated tumors that have an increased proliferation rate and induce neovascularization, compared with the surrounding liver. But at this stage, they maintain a near-normal apoptosis/mitosis ratio and uncommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…23 Clearly, HCC recurrence after OLT represents a complex interplay of host-and tumor-related factors, the nature of which has yet to be fully elucidated. 19 In conclusion, our results support a modest expansion of the tumor size limits of the Milan criteria (the UCSF criteria) while still preserving acceptable survival after OLT. The expanded criteria offered the benefits of OLT to about 20% of our patients who would have otherwise been excluded from OLT under the more restrictive Milan criteria.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…23 Clearly, HCC recurrence after OLT represents a complex interplay of host-and tumor-related factors, the nature of which has yet to be fully elucidated. 19 In conclusion, our results support a modest expansion of the tumor size limits of the Milan criteria (the UCSF criteria) while still preserving acceptable survival after OLT. The expanded criteria offered the benefits of OLT to about 20% of our patients who would have otherwise been excluded from OLT under the more restrictive Milan criteria.…”
Section: Discussionsupporting
confidence: 69%
“…Furthermore, the Pittsburgh group observed that in 30% of the cases, the same combination of tumor characteristics in their prognostic model did not correlate well with clinical outcome as predicted. 19 Several published studies have found poorly differentiated histologic grade, 17,20,21 or microvascular invasion, 11,22 or both 23 to be independent predictors of impaired survival after OLT. The present study suggests a strong correlation of these histologic features with more advanced tumor stage exceeding the limits of the Milan and UCSF criteria, albeit to a lesser degree for the latter (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that certain histological features may be predictive of a tumor's aggressiveness, such as degree of differentiation and low apoptosis-mitosis ratio. 21 However, more studies are needed to identify factors that would stratify HCC tumors on their predicted growth rates to help triage donor organs more effectively. Until then, policymakers may want to consider adding a MELD adjustment factor for the presence of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…5 Similarly, HCC development has been speculated to be a multistage process because of its progressively pathologic morphology. 6 However, the stepwise progress in human HCC is ill defined and specific genetic changes associated with HCC progression remain vague. 7 This has been explained by the finding that most HCC tissue specimens used for analysis may be at an advanced stage and most of the changes found in these lesions can be secondary.…”
mentioning
confidence: 99%